PENGARUH RASIO PROFITABILITAS, RASIO AKTIVITAS TERHADAP FINANSIAL DISTRESS DENGAN TAX AVOIDANCE SEBAGAI VARIABEL MODERASI (Studi pada Perusahaan Sektor Properties dan Real Estate yang Terdaftar di BEI Tahun 2020-2024) - Vivi Luthfiani; Meutia Riany (UNIVERSITAS DHARMAWANGSA, 2026)
This study is motivated by the increasing financial vulnerability of property and real estate companies in Indonesia amid economic uncertainty, which raises the risk of financial distress. The purpose of this study is to examine the effect of profitability and activity ratios on financial distress, with tax avoidance as a moderating variable, in property and real estate companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. Profitability is proxied by Return on Assets (ROA), activity ratio is measured using Total Asset Turnover (TATO), financial distress is assessed using the Altman Z-Score model, and tax avoidance is proxied by the Cash Effective Tax Rate (CETR). This research employs a quantitative approach using Moderated Regression Analysis (MRA). The sample is selected through purposive sampling, consisting of companies that published complete annual financial statements during the observation period. Secondary data are obtained from the official IDX website and analyzed using SPSS software. The results indicate that profitability has a positive and significant effect on financial distress, while the activity ratio has a negative and significant effect on financial distress. Furthermore, tax avoidance is proven to moderate the relationship between profitability and financial distress by weakening the effect, but it does not moderate the relationship between activity ratio and financial distress. These findings imply that tax avoidance plays a partial moderating role and highlight the importance of financial performance and tax strategies in managing financial distress risk within the property and real estate sector.